Taiwan Junior High School Adolescents' Epistemological Beliefs toward Mathematics and Science. (6th February 2012) - Lee, Chun-Yi; Yuan, Yuan
Abstract : Few previous studies have compared students' epistemological beliefs in mathematics with those in science. To ascertain the discipline and gender differences on students' epistemological beliefs, this study conducted a survey with 495 Taiwanese ninth graders in junior high school. Findings show that female students express the stronger belief that science learning occurs in a quick fashion as compared with the view that mathematics learning occurs in a quick fashion, both male and female students express the stronger belief that mathematics knowledge is certain as compared with the view that science knowledge is certain, and male students express the stronger belief that science knowledge is simple and the ability to learn science is fixed as compared with the view that mathematics knowledge is simple and the ability to learn mathematics is fixed. Male students were also in more agreement in their belief about quick learning, certain knowledge, simple knowledge, and the innate ability of mathematics, as well as certain knowledge, simple knowledge, and the innate ability of science, than were female students. This study also revealed that students' beliefs about knowledge are domain-specific, but some evidence of domain-general beliefs also exists.